The Rise of West Lake : A Cultural Landmark in the Song Dynasty - Duan, Xiaolin (Book collections on Project MUSE., 2020)
"West Lake, near scenic Hangzhou on China's east coast, has been a major tourist site since the twelfth century and a model for idealized nature. Visitors boat to its islands, stroll through its gardens, worship in its temples, and celebrate it in poetry and painting. Xiaolin Duan examines the interplay between cultural norms and the natural environment around West Lake during the Song dynasty (960-1279). After the Song lost north China to the Jurchens and the imperial court fled south, a new capital was established at Hangzhou in 1127, making the area the national political and cultural center. Duan shows how leisure activities in, on, and around West Lake influenced visitors' conceptualization of nature and sparked the emergence of the lake as a tourist destination, and how the natural landscape played an active role in shaping social pursuits and cultural constructs. Incorporating evidence from miscellanies, local and temple gazetteers, paintings, maps, poems, and anecdotes, she explores the complexity of the lake as an interactive site where ecological and economic concerns contended and where spiritual pursuits overlapped with aesthetic ones. The book will appeal to readers interested in urban and environmental history, cultural geography, and the sociology of tourism"--